2001
DOI: 10.1063/1.1397286
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen incorporation in ultrathin gate dielectrics: A comparison of He/N2O and He/N2 remote plasma processes

Abstract: Ultrathin Si oxynitride films grown by low-temperature remote plasma processing were examined by on-line Auger electron spectroscopy and angle-resolved x-ray photoelectron spectroscopy to determine the concentration, spatial distribution, and chemical bonding of nitrogen. The films were grown at 300 °C on Si(100) substrates using two radio-frequency remote plasma processes: (i) He/N2O remote plasma-assisted oxidation (RPAO) and (ii) two-step remote plasma oxidation/nitridation. A 5 min He/N2O RPAO process prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For ultrathin SiO 2 films ͑Ͻ1 nm͒ processed at 0.3 Torr, previous experiments have shown that nitrogen diffuses through the superficial oxide, and bonds at the Si-SiO 2 interface. 21,22 These observations suggest that the nitridation mechanism changes from ''nondiffusive'' ͑charged particle-assisted͒ to ''diffusive'' ͑presumably involving neutral N species͒ as the process pressure is increased from 0.1 to 0.3 Torr. The very low nitridation rate measured at 0.1 Torr using a N 2 remote plasma indicates that He dilution provides a strong nitridation rate enhancement.…”
Section: Discussionmentioning
confidence: 95%
“…For ultrathin SiO 2 films ͑Ͻ1 nm͒ processed at 0.3 Torr, previous experiments have shown that nitrogen diffuses through the superficial oxide, and bonds at the Si-SiO 2 interface. 21,22 These observations suggest that the nitridation mechanism changes from ''nondiffusive'' ͑charged particle-assisted͒ to ''diffusive'' ͑presumably involving neutral N species͒ as the process pressure is increased from 0.1 to 0.3 Torr. The very low nitridation rate measured at 0.1 Torr using a N 2 remote plasma indicates that He dilution provides a strong nitridation rate enhancement.…”
Section: Discussionmentioning
confidence: 95%
“…19 The higher concentration of reactive oxygen species thus results in more extensive replacement of nitrogen atoms in the bulk, and especially in the interfacial region of nitrided hafnium oxide films with the silicon substrate. 26,27 Higher concentration of reactive oxygen species also results in more completely oxidized hafnium ions in the interfacial regions of films deposited in nitrous oxide. For the above reasons, lower nitrogen concentrations exist at the interface of nitrous oxide-deposited films with silicon relative to those of films deposited in oxygen.…”
Section: F2mentioning
confidence: 99%
“…N 2 O is completely dissociated in the plasma at these power densities, and the signal at m / z (mass-tocharge ratio͒ = 44 is due to CO 2 + formed from the reaction of atomic oxygen with residual carbon on the walls of the reactor chamber. Some peaks in the region between 300 and 500 nm may be caused by the first negative system of the 19 Each spectra also shows a small peak at 821 nm that is attributed to atomic N. 20 No emission from NO was detected in this system. 1 were only weakly impacted by power over the range studied.…”
Section: A Icp Source Characterizationmentioning
confidence: 83%